STRATEGIC MODEL OF LEARNING IMPLEMENTATION OF MISSION-BASED MBKM, ACADEMIC LEADERSHIP, COLLABORATION, COMMITMENT, AND SUSTAINABILITY WITH THE INFLUENCE OF INFORMATION TECHNOLOGY IN HIGH SCHOOLS - Dunan, Hendri; Sanusi, Anuar; AA, Iskandar; Hairani, Tuti (International Journal of Artificial Intelligence Research, 2025)
This research aims to develop and analyze a strategy model for implementing MBKM learning, namely university mission, academic leadership, collaboration, commitment, and sustainability, as well as the impact of the use of information technology. The research results show that leadership and information technology variables are strategic variablesfor improving learning strategies. This is because the research results of these variables have a significant influence. Meanwhile, information technology variables are not effective as moderatorvariablesontherelationshipbetweencommitmentandlearningstrategiesbecause the research results have a weak and negative influence. Collaboration and commitment variables are appropriate variables for learning strategies. This collaboration variable has a positive and significant influence on learning strategies in the context of this research, meaning that collaboration plays an important role in influencing learning strategies. Commitment is a very important factor in influencing learning strategies. Learning strategy variableshaveasignificantpositiveinfluenceonsustainabilityinthiscasethroughlearning strategies, which have been proven to have a significant positive impact on sustainability however,itisimportanttocontinuetocarryoutfurtherresearchanddevelopmenttosupport sustainability efforts on an ongoing basis. The information technology variable has a significant influence as a moderator on the relationship between learning strategies and sustainability, meaning that the interaction between learning strategies and information technologyappearstohaveastrongandnegativeinfluenceonsustainability.Thekeyfactors are mission, academic leadership, collaboration, commitment, and sustainability, and it can help universities to more effectively adapt and implement MBKM policies to increase autonomy and flexibility in highereducation